P75 PRELIMINARY FINDINGS OF THE DAVIDS REGISTRY (DYEVERT TO AVOID UNNECESSARY CONTRAST MEDIA DELIVERY DURING PCI SANREMO REGISTRY). (18th May 2022) - Vergni, F; Arioti, M; Boasi, V; Sanchez, F; Leoncini, M; Ferrari, F
Abstract: Background: Contrast–induced acute kidney injury (CI–AKI) is a percutaneous coronary intervention's (PCI) feared complication, linked to increased morbidity and mortality. Many risk factors have been identified. Amongst procedural variables contrast media (CM) volume is one of the most predictive. An easy–to–use and effective CM sparing device would represent a valuable tool in the cath–lab armamentarium. Aim: To evaluate the effectiveness of the DyeVert Power XT system in reducing CM delivery during PCI in pts at high risk of CI–AKI, consequently reducing the risk itself. Methods We collected clinical, laboratory, instrumental, procedural and outcome data of 75 consecutive patients (pts) who underwent PCI with the use of the DyeVert system between September 2020 and December 2021. We also compared these data in two groups of patients, divided according to CI–AKI onset. Inclusion criteria were reduced estimated glomerular filtration rate (eGFR) – defined as creatinine clearance (CrCl) <60 mL/min/m2 – and/or need for a complex PCI – chronic total occlusion (CTO), previous coronary artery bypass graft (CABG) or diffuse multivessel disease (MVD) – with the likelihood to receive a high amount of CM. Results: Clinical data are shown in Table 1. Lab and instrumental data are shown in Table 2. Procedural data are shown in Table 3. In–hospital events are shown in Table 4. CI–AKI predictors at multivariate analysis are shown in Table 5. Median dose of CM delivered was 255 ml while CM spared with DyeVert was 110 ml (43% volume reduction, median 1 point reduction in Mehran score). Turning to outcomes 11 pts (14.7%) experienced AKI stage I according to Kidney Disease – Improving Global Outcomes (KDIGO) definition, whilst only 3 pts (4%) and 2 pts (2.7%) experienced stage 2 and 3 AKI. At follow–up there were 4 in–hospital deaths, none linked to deteriorating renal function. Conclusions: DyeVert use was simple and effective in cutting delivered CM amount, with preserved image quality according to the operators judgement, however the reduction in Mehran score was not sufficient to affect risk class in pts experiencing CI–AKI versus those who did not.